SOSIALISASI SERTIFIKASI HALAL BAGI PELAKU UMKM DI KECAMATAN TAJURHALANG, KABUPATEN BOGOR - Amelya Setyawati; Yeni Kurniati; Dhita Sari siregar; Hafzialman Hafzialman; Rima Hidayati; Aldrian Faqih Zanuar; Nugraha Susanto; Irma Handayana (Bajang Institute, 2025)
This socialization activity aimed to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Tajurhalang District, Bogor Regency, regarding the importance of halal certification. The program provided education on registration processes, benefits, and guidelines for preparing Halal Product Assurance System (SJPH) documents. Methods included seminars, technical training, and mentoring. A total of 46 MSME participants attended this activity held on Sunday, January 12, 2025. Results indicated improved participant understanding of the benefits and procedures of halal certification. This initiative is expected to significantly increase the number of halal-certified products from MSMEs in Tajurhalang.